2010
DOI: 10.1016/j.cmet.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Residues on Niemann-Pick C2 Essential for Hydrophobic Handoff of Cholesterol to NPC1 in Lysosomes

Abstract: Summary Water-soluble Niemann-Pick C2 (NPC2) and membrane-bound NPC1 are cholesterol-binding lysosomal proteins required for export of lipoprotein-derived cholesterol from lysosomes. The binding site in NPC1 is located in its N-terminal domain (NTD), which projects into the lysosomal lumen. Here, we perform alanine-scanning mutagenesis to identify residues in NPC2 that are essential for transfer of cholesterol to NPC1(NTD). Transfer requires three residues that form a patch on the surface of NPC2. We previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
231
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(244 citation statements)
references
References 19 publications
12
231
0
1
Order By: Relevance
“…In summary, a model has been proposed for the transfer of cholesterol from NPC2 to NPC1 proteins (6,14,15). The biochemical findings reported here support the proposed directionality of this transfer process and provide human genetic evidence regarding the importance of the interaction between NPC1 and NPC2 proteins to accomplish cholesterol delivery from lysosomes into the cytoplasm.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In summary, a model has been proposed for the transfer of cholesterol from NPC2 to NPC1 proteins (6,14,15). The biochemical findings reported here support the proposed directionality of this transfer process and provide human genetic evidence regarding the importance of the interaction between NPC1 and NPC2 proteins to accomplish cholesterol delivery from lysosomes into the cytoplasm.…”
Section: Discussionsupporting
confidence: 64%
“…Wang et al (15) also identified NPC1 residues L175/L176 and E191/Y192 as being critical for receipt of cholesterol from NPC2. Moreover, when introduced into cells, the L175Q/L176Q mutant NPC1 protein cannot restore egress of cholesterol from lysosomes (15). This observation is consistent with a requirement for interaction between NPC1 and NPC2 proteins as part of the normal cholesterol export process.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…no. 134113; Abcam) or 2 μg/mL mouse monoclonal IgG-13G4 against NPC2 (36). Bound antibodies were visualized by chemiluminescence (SuperSignal West Pico Chemiluminescent Substrate; Thermo Scientific) after a 1 h incubation with a 1:5,000 dilution of either donkey anti-mouse or goat anti-rabbit IgG conjugated to horseradish peroxidase (Jackson ImmunoResearch).…”
Section: Methodsmentioning
confidence: 99%